Padrões de sibilância respiratória do nascimento até o início da adolescência estudo longitudinal das crianças nascidas em 1993 na cidade de Pelotas-RS - García, Adriana Muiño (2006)
Wheezing patterns during childhood have important prognostic implications. The aim of this study was to measure the prevalence of wheezing patterns in a sub-sample of the 1993 Pelotas, Brazil, birth cohort, interviewed at birth , 6 and 12 month, 4 and 10-12 years of age. The wheezing patterns studied were: transient, persistent, late onset and recurrent. The total of the sub-sample was 897 children (20% systematic sample from the original cohort) with the prevalence and 95% confidence interval of wheezing patterns as follows: transient 44.7% (40.7-47.2); persistent 6.4% (4.8-8.0); late onset 3.3% (2.2-4.5); recurrent 4.1% (2.8-5.4). The independent variables associated with the wheezing patterns were: a) transient wheeze: low family income, shorter duration of breast-feeding, respiratory infections (6 and/or 12 months) and family history of asthma; b) persistent: male sex, asthma during pregnancy, respiratory infections in infancy and family history of asthma (4 and 10-12 years; c) late onset: family history of asthma (10-12 years old), medical diagnoses of rhinitis (10-12 years old) and as protective factors respiratory infections in infancy and a medical diagnosis of eczema (at adolescence); d) recurrent: smoking during pregnancy and having no asthma in the family. Identifying wheezing patterns and associated factors allow us to adopt preventive measures and to avoid lung function deterioration in adult life.